Anthropozentrismus (in) der Krise: Warum Probleme nicht mit der Denkweise gelöst werden können, die sie auch hervorgerufen hat [Anthropocentrism in crisis. Why problems cannot be solved with the same mindset that created them] - Bossert, Leonie N.; Schlegel, Lena (GAIA-Ecological Perspectives For Science and Society, 2022)
Reaktion auf U. Eser in GAIA 30/4 (2021): Mit Umweltethik gegen Pandemien? Zum Unterschied von Ethik und Politik. Anthropozentrische Perspektiven können nicht ausreichend zur Lösung sozial-ökologischer Krisen beitragen, da sie selbst Teileines krisenhaften Systems gesellschaftlicher Naturverhältnisse sind. Daher ist eine Ausweitung des Anthropozentrismus-Begriffsmoralphilosophisch problematisch. Um die Transformation gesellschaftlicher Naturverhältnisse differenziert zu bewerten,ist vielmehr eine nichtanthropozentrische intersektionale Perspektive in der Umweltethik hilfreich<br
Created from Fastlane, Scopus look-up
Keywords: animal ethics; environmental ethics; socio-ecological crises

Between climates of fear and blind optimism: the affective role of emotions for climate (in)action - Schlegel, Lena (Geographica Helvetica, 2022)
Emotions affect how humans relate to others and define their place in the world. They thus shape responses to socio-ecological problems like climate change. In spite of the overwhelming knowledge and concern about climate change, a lack of appropriate moral and political consequences prevails in most contemporary societies. Instead of trying to explain climate inaction as a result of (un)awareness, this paper introduces a new perspective by conceptualising climate inaction as an active social process animated by emotions. Drawing on an interdisciplinary and radically relational perspective, I grasp climate inaction as a product of more-than-human intra-action and explore the affective role of emotions within this production. To illustrate how emotions energise climate inaction, I sketch how fear, grief, and hope animate current climate responses.
Created from Fastlane, Scopus look-up

Mit Umweltethik gegen Pandemien: Warum Tierrechte und Naturschutz auch den Menschen nutzen [Environmental ethics on pandemics: why even humans can benefit from animal rights and nature conservation] - Bossert, Leonie N.; Schlegel, Lena (GAIA-Ecological Perspectives For Science and Society, 2021)
Das Entstehen von Pandemien wie COVID-19 wird auch durch menschliche Eingriffe in die Natur begünstigt. Die Umweltethik bietet Argumente, um unseren Umgang mit Pflanzen und Tieren zu bewerten und einen schonenden, respektvollen Umgang mit der außermenschlichen Natur zu befördern. So sollte etwa tierethischen Belangen mehr Aufmerksamkeit geschenkt werden ‐ im Interesse der Tiere wie auch zur Prävention von Pandemi
Created from Fastlane, Scopus look-up
Keywords: Animal ethics; COVID-19 pandemic; Environmental ethics; Socio-ecological crises

Multispecies Grief in the Wake of Megafires - Otjen, Nathaniel; Schlegel, Lena; Lambert, Shannon; Della Bosca, Hannah; Verlie, Blanche (2023)